Biochemical effects of the pharmaceutical drug paracetamol on Anguilla anguilla - Nunes, Bruno
The ever-increasing presence of pharmaceutical drugs in the environment is a motif of concern, and humanuse drugs are of particular importance. This is the case of paracetamol, a widely employed drug in human therapeutics, as analgesic and antipyretic, whose toxicity on aquatic organisms is still not fully characterized. The present study aimed to assess the toxic deleterious effects of paracetamol on European eel, Anguila anguilla, by using a comprehensive battery of antioxidant biomarkers (activities of enzymes such as catalase (CAT) and glutathione S-transferases (GSTs)), and the quantification of oxidative damage (measurement of levels of lipid peroxidation (thiobarbituric acid reactive substances (TBARS) assay)). Other biochemical effects elicited by this substance were also quantified, in terms of anaerobic respiration (activity of lactate dehydrogenase, LDH) and neurotoxicity (acetylcholinesterase, AChE, activity). The obtained results showed the occurrence of an oxidative base response, and paracetamol also seemed to inhibit AChE, showing that this drug can also elicit neurotoxicity. The lack of response by both CAT and LDH show that, despite the occurrence of toxicity, eels have detoxification mechanisms that are effective to cope with paracetamol, preventing additional deleterious alterations, including in the main pathway by which they obtain energy.